2009
DOI: 10.1007/s12664-009-0086-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of bleeding after esophageal variceal eradication in patients with extrahepatic portal venous obstruction; a 20-year follow-up

Abstract: EST is an effective treatment modality for bleeding esophageal varices due to EHPVO. During a follow-up of nearly 20 years after variceal eradication, only about one-sixth of the patients had recurrence of gastrointestinal bleeding. Bleeding was unusual after 10 years had passed since initial variceal eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
(36 reference statements)
0
26
3
3
Order By: Relevance
“…114 Bleeding after initial variceal eradication occurs usually within first 4-10 years and the risk of bleeding reduces as age progresses especially after 10 years. 115 Liver dysfunction in long term is a concern and other long term consequences in nutrition, mental function and portal biliopathy.…”
Section: Chronic Portal Vein Thrombosismentioning
confidence: 99%
“…114 Bleeding after initial variceal eradication occurs usually within first 4-10 years and the risk of bleeding reduces as age progresses especially after 10 years. 115 Liver dysfunction in long term is a concern and other long term consequences in nutrition, mental function and portal biliopathy.…”
Section: Chronic Portal Vein Thrombosismentioning
confidence: 99%
“…In the younger age group (<20yrs), early appearance of varices / PHTN is due to NCPF (Non-cirrhotic portal fibrosis) and EHPVO (Extra-hepatic portal vein obstruction) which could be attributed to nutritional deficiencies / infection. 20,21 Highest incidence of infections was to be found in 31-40-year age group. The patients who were immunocompromized/susceptible to infection showed infections like candidiasis.…”
Section: -18mentioning
confidence: 99%
“…Though many recent studies have shown almost comparable rates of control of acute bleed, rebleed and overall long term survival with endoscopic variceal sclerotherapy, 13 yet in a country like India, where expert endoscopic therapy and blood banking facilities in many remote areas are still sub optimal, a onetime surgical procedure in the form of a splenectomy and portosystemic shunt, in those with good liver function like EHPVO or NCPF is still a better option. Moreover, the control of portal hypertensive gastropathy, portal biliopathy and growth retardation in these patients can be addressed only by a portosystemic shunt.…”
Section: Long Term Survivalmentioning
confidence: 99%